Differential Influence of Physical Activity on Cardiopulmonary Performance and Stroke Volume Assessed at Cardiopulmonary Exercise Test in Pectus Excavatum: A Pilot Study - Casatori, Lorenzo; Pellegrino, Alessio; Messineo, Antonio; Ghionzoli, Marco; Facchini, Flavio; Modesti, Alessandra; Modesti, Pietro Amedeo (Frontiers in Physiology, 2022)
Background: Exercise training increases muscle VO2 by increasing O2 transport and O2 uptake while cardiac output increase might be limited by the conformation of the chest in subjects with pectus excavatum (PE). Aims: The aim of the present study was to investigate the influence of physical activity (PA) on functional parameters of cardiopulmonary performance and stroke volume obtained at Cardiopulmonary Exercise Test (CPET) in PE. Methods and Procedures: A cohort of adolescents (15 with PE and 15 age- and sex-matched healthy controls, HC) underwent Cardiopulmonary Exercise Test (CPET) and administration of the International Physical Activity Questionnaire – Short Form (IPAQ-SF) with estimation of weekly PA (METs h-1·week-1). Determinants of CPET parameters were investigated with multivariable linear regression analysis. Results: As expected, when compared to HC, PE had lower VO2 max (37.2±6.6 vs 45.4±6.4 mL·kg-1·min-1, p<0.05), and VO2/HR max (O2 pulse, 12.1±2.4 vs 16.2±3.6 mL·min-1·bpm-1, p<0.05). Importantly, physical activity level was a predictor of VO2 max (adjusted for sex, body mass index, FEV1%, and presence of PE, β=0.085; 95% Cl 0.010 to 0.160, p=0.029) whereas O2 pulse was independent from PA level (β=0.035; 95% Cl -0.004 to 0.074). Conclusion: Physical activity is a determinant of VO2 max (cardiopulmonary performance), whereas it appears not to affect O2 pulse (a measure of stroke volume at peak exercise) related to constrained diastolic filling in PE.